2007
DOI: 10.1159/000099025
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Tinnitus Revealed at 2 kHz Range by Bilateral Lower DPOAEs in Normal Hearing Subjects with Noise Exposure

Abstract: We investigated potential markers of susceptibility to tinnitus in a group of normal hearing young pilots aged 25–35 years and with 8 ± 5 years of aircraft noise exposure. 316 pilots were interviewed about their tinnitus status and were tested for hearing thresholds (audiograms) and distortion products otoacoustic emissions (DPOAE-grams). There was no subject with permanent tinnitus. 23% reported having occasionally perceived tinnitus after flight missions and 77% reported never having experienced tinnitus aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
2
26
0
9
Order By: Relevance
“…This phenomenon has been indirectly reported in the vast majority tinnitus related publications but has not been studied systematically. For example, most clinical cases reported a strong correlation between hearing loss and tinnitus (Weisz et al, 2006), whereas other studies described tinnitus cases where tinnitus patients demonstrated no audiometric deficits (Schmuziger et al, 2006; Job et al, 2007; Langers et al, 2012). The diversity of tinnitus pathologies seen in the current study and other animal studies (Longenecker and Galazyuk, 2011; Coomber et al, 2014; Hickox and Liberman, 2014; Ropp et al, 2014) could be explained by a number of phenotypic factors including differences in individual animals in stress levels, unintentional noise exposure, differential peripheral damage, or unique animal-specific maladaptive neuroplasticity pattern caused by sound exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been indirectly reported in the vast majority tinnitus related publications but has not been studied systematically. For example, most clinical cases reported a strong correlation between hearing loss and tinnitus (Weisz et al, 2006), whereas other studies described tinnitus cases where tinnitus patients demonstrated no audiometric deficits (Schmuziger et al, 2006; Job et al, 2007; Langers et al, 2012). The diversity of tinnitus pathologies seen in the current study and other animal studies (Longenecker and Galazyuk, 2011; Coomber et al, 2014; Hickox and Liberman, 2014; Ropp et al, 2014) could be explained by a number of phenotypic factors including differences in individual animals in stress levels, unintentional noise exposure, differential peripheral damage, or unique animal-specific maladaptive neuroplasticity pattern caused by sound exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Following this damage, the central auditory system increases its gain to compensate for the reduced sensorineural input from the cochlea, which can lead to tinnitus (Salvi et al, 2000; Schaette and McAlpine, 2011; Auerbach et al, 2014). In most clinical cases, there is a strong correlation between hearing loss and tinnitus (Lockwood et al, 2002), but interestingly, this is not always true, as some patients with clinically normal thresholds have tinnitus (Weisz et al, 2006; Job et al, 2007). Just as in humans (Hall et al, 2016), the extent of peripheral damage and central plasticity in individual animals of the AOE model differs greatly, leading to a heterogeneous population of hearing loss (HL) and/or tinnitus pathology (Longenecker and Galazyuk, 2011; Singer et al, 2013; Hickox and Liberman, 2014; Knipper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4 ). Despite the fact that a relationship between otoacoustic emissions and tinnitus has yet to be established, altered otoacoustic emissions in individuals with tinnitus and normal hearing have been described in the literature [Shiomi et al, 1997;Onishi et al, 2004;Gouveris et al, 2005;Ozimek et al, 2006;Job et al, 2007;Ami et al, 2008]. Ami et al [2008] stated that subtle damage to the outer hair cells can provoke tinnitus before the impairment alters the audiogram.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in cochlear function was demonstrated even in individuals with tinnitus and normal hearing [Shiomi et al, 1997;Onishi et al, 2004;Gouveris et al, 2005;Ozimek et al, 2006;Job et al, 2007;Ami et al, 2008]. Weisz et al [2006] demonstrated that patients with tinnitus and normal hearing do not necessarily present peripheral auditory integrity, which underscores the importance of investigating cochlear function in patients presenting such characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 12 international papers in the Medline database, 6 used DPOAE24 25 19 20 27 30 and 6 used both tests18 28 21 12 29 17 13 26.…”
Section: Resultsmentioning
confidence: 99%